2001
DOI: 10.1002/jclp.1128
|View full text |Cite
|
Sign up to set email alerts
|

Is EMDR an exposure therapy? A review of trauma protocols

Abstract: This article presents the well established theoretical base and clinical practice of exposure therapy for trauma. Necessary requirements for positive treatment results and contraindicated procedures are reviewed. EMDR is contrasted with these requirements and procedures. By the definitions and clinical practice of exposure therapy, the classification of EMDR poses some problems. As seen from the exposure therapy paradigm, its lack of physiological habituation and use of spontaneous association should result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 65 publications
(80 reference statements)
0
65
0
2
Order By: Relevance
“…Unlike exposure therapies, EMDR therapy uses free association techniques that often only briefly access details of traumatic memories, instead of repetitive exposure to traumatic memories. Experimental studies showed that the underlying mechanism of EMDR did not seem to be based on habituation (e.g., Leer, Engelhard, Altink, & Van den Hout, 2013), and would therefore be less suited for promoting habituation and symptom reduction compared exposure-based therapies (McGuire, Lee, & Drummond, 2014;Rogers & Silver, 2002). Alternatively, the inferior EMDR results might be attributed to study design characteristics.…”
Section: Discussionmentioning
confidence: 91%
“…Unlike exposure therapies, EMDR therapy uses free association techniques that often only briefly access details of traumatic memories, instead of repetitive exposure to traumatic memories. Experimental studies showed that the underlying mechanism of EMDR did not seem to be based on habituation (e.g., Leer, Engelhard, Altink, & Van den Hout, 2013), and would therefore be less suited for promoting habituation and symptom reduction compared exposure-based therapies (McGuire, Lee, & Drummond, 2014;Rogers & Silver, 2002). Alternatively, the inferior EMDR results might be attributed to study design characteristics.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, although reliving often occurs during EMDR the dual attention processing eventually creates a sense of distance and mindfulness (Lee, Taylor & Drummond, 2006) . The occurrence of free association is thought to demonstrate successful consolidation between the event and the client's current knowledge networks (Lee, 2006;Lee et al, 2008;Rogers & Silver, 2002).…”
Section: Movement Desensitisation and Reprocessing (Emdr) Or Trauma-fmentioning
confidence: 99%
“…Whether its efficacy stems from the fact that it is yet another variant of exposure therapy (with some ingredients of cognitive therapy) or that it is based on new principles is unclear" (Shalev, Friedman, Foa, & Keane, 2000, p. 366). This question is of particular interest since EMDR calls for interrupted rather than prolonged exposure and elements of free association (Rogers et al, 1999;Rogers & Silver, 2002;Shapiro, 1995Shapiro, , 1999Shapiro, , 2001a, both of which are inconsistent with the principle and practice long espoused in the exposure literature (Boudewyns & Hyer, 1990Chaplin & Levine, 1981;Chemtob et al, 2000;Eysenck, 1979;Foa, Steketee, & Rothbaum, 1989;Keane & Kaloupek, 1982;Lyons & Scotti, 1995;Marks, 1972;Marks et al, 1998;Rachman, 1980). Any effective clinical method consists of a number of constituents whose relative weightings and mutual interactions are initially unknown.…”
Section: Component Analysesmentioning
confidence: 99%